An on-skin electrode with anti-epidermal-surface-lipid function based on a zwitterionic polymer brush - He, Ke (2021)
On‐skin flexible devices provide a noninvasive approach for continuous and real‐time acquisition of biological signals from the skin, which is essential for future chronic disease diagnosis and smart health monitoring. Great progress has been achieved in flexible devices to resolve the mechanical mismatching between conventional rigid devices and human skin. However, common materials used for flexible devices including silicon‐based elastomers and various metals exhibit no resistance to epidermal surface lipids (skin oil and grease), which restricts the long‐term and household usability. Herein, an on‐skin electrode with anti‐epidermal‐surface‐lipid function is reported, which is based on the grafting of a zwitterionic poly(2‐methacryl‐oyloxyethyl, methacryloyl‐oxyethyl, or meth‐acryloyloxyethyl phosphorylcholine) (PMPC) brush on top of gold‐coated poly(dimethylsiloxane) (Au/PDMS). Such an electrode allows the skin‐lipids‐fouled surface to be cleaned by simple water rinsing owing to the superhydrophilic zwitterionic groups. As a proof‐of‐concept, the PMPC‐Au/PDMS electrodes are employed for both electrocardiography (ECG) and electromyography (EMG) recording. The electrodes are able to maintain stable skin‐electrode impedance and good signal‐to noise ratio (SNR) by water rinsing alone. This work provides a material‐based solution to improve the long‐term reusability of on‐skin electronics and offers a unique prospective on developing next generation wearable healthcare devices.